Stable Copper Tin Sulfide Nanoflower Modified Carbon Quantum Dots for Improved Supercapacitors - Zhen Bi; Lanyan Huang; Chaoqun Shang; Xin Wang; Guofu Zhou (Journal of Chemistry)
Copper tin sulfides (CTSs) have widely been investigated as electrode materials for supercapacitors owing to their high theoretical pseudocapacitances. However, the poor intrinsic conductivity and volume change during redox reactions hindered their electrochemical performances and broad applications. In this study, carbon quantum dots (CQDs) were employed to modify CTSs. The structures and morphologies of obtained materials were characterized by X-ray diffraction (XRD) and transmission electron microscopy (TEM). XRD revealed CTSs were composed of Cu2SnS3 and Cu4SnS4, and TEM suggested the decoration of CQDs on the surface of CTSs. With the decoration of CQDs, CTSs@CQDs showed a remarkable specific capacitance of 856 F·g−1 at 2 mV·s−1 and a high rate capability of 474 F·g−1 at 50 mV·s−1, which were superior to those of CTSs (851 F·g−1 at 2 mV·s−1 and 192 F·g−1 at 50 mV·s−1, respectively). This was mainly ascribed to incorporation of carbon quantum dots, which improved the electrical conductivity and alleviated volume change of CTSs during charge/discharge processes.